A dual-responsive pH-sensor and its potential as a universal probe for assays of pH-changing enzymes - Thai, Hien Bao Dieu; Yu, Jin Kyung; Park, Yeon-Joon; Ahn, Dae-Ro (Royal Society of Chemistry, 2015)
We described a dual turn-on probe sensitive to both acidity and basicity, which could be designed by connecting a fluorophore to a quencher via metal-ligand interaction. Atto488-labeled nitrilotriacetic acid and polyhistidine peptide were used as the fluorophore and the quencher, respectively, and linked to each other by coordination with a cobalt(II) ion. After preparation of the probe, the pH-sensitive dual turn-on property of the probe has been successfully observed upon responding to both acidity and basicity of the solution. The probe has been employed as a signal reporter in assays of pH-changing enzymes such as penicillinase generating acidity and adenosine deaminase generating basicity. Furthermore, the practical utility of the probe was also demonstrated by utilizing the probe in the discrimination of beta-lactamase-producing bacteria.
Keywords: SPECTRUM BETA-LACTAMASES; CLAVULANIC ACID; RAPID DETECTION; ENTEROBACTERIACEAE; DEAMINASE